National safe motherhood survey, 1993. (National Statistics Office, 1994)
"This report summarizes the findings of the 1993 National Safe Motherhood Survey (SMS) undertaken by the National Statistics Office in collaboration with the Department of Health, the University of the Philippines, and other concerned agencies in the Philippine government. The 1993 SMS was a follow-up on the 1993 National Demographic Survey (NDS), which is a part of the worldwide Demographic and Health Survey (DHS) program. This program is designed to collect, analyze, and disseminate demographic data on fertility, family planning, and maternal and child health. The SMS covered a national sample of about 8,500 women, 1,549 of which ever having pregnancy outcome. This survey provides a data set unique in its ability to describe the maternal health situation in the Philippines as well as to answer important questions about relationships between women's health status, use of services, and socio-demographic characteristics." There are tables, figures, and even the map of the Philippines.